Scaling up Family Medicine in Uganda - Innocent K. Besigye; Jane F. Namatovu (AOSIS, 2014)
It is evident that politicians, health managers and academics are realising the potential contribution of Family Medicine to health systems in sub-Saharan Africa. The challenge is in training institutions to recruit and train enough Family Physicians in order to meet expectations. The 3rd Family Medicine Conference in Uganda, held in October 2013, explored innovative ways of scaling up Family Medicine training and practice in Uganda.